2018
DOI: 10.2118/191130-pa
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of Distributed Temperature Sensing and Distributed Acoustic Sensing for the Application of Gas Lift Surveillance

Abstract: Summary Fiber-optic (FO) -based sensing technologies such as distributed temperature sensing (DTS) or distributed acoustic sensing (DAS) for well surveillance are attractive because they offer a continuous collection of real-time downhole data without the need for well intervention, thus avoiding production deferment. An example is the application of DTS and DAS for gas lift performance monitoring in oil producers by measuring the thermal and acoustic effects from the flow of lift gas through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Even though, the DTS was derived from commercial thermal simulator [ 34 ], the work shows a promising result on combining SoS from DAS and from simulated DTS to provide an accurate multiphase estimation. Hemink et al [ 88 ], on the other hand, showed that from actual DTS does not always provide reliable results as a straightforward thermal model to identify gas-injection. Instead, the work proposed an improvement by considering the temperature response measured by DTS where the fibre is clamped and bending away from the tubing.…”
Section: Physical Flow Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though, the DTS was derived from commercial thermal simulator [ 34 ], the work shows a promising result on combining SoS from DAS and from simulated DTS to provide an accurate multiphase estimation. Hemink et al [ 88 ], on the other hand, showed that from actual DTS does not always provide reliable results as a straightforward thermal model to identify gas-injection. Instead, the work proposed an improvement by considering the temperature response measured by DTS where the fibre is clamped and bending away from the tubing.…”
Section: Physical Flow Modellingmentioning
confidence: 99%
“…Thermal-and-hydraullic modelling [88] 2018 DAS and DTS Thorough analysis on combining DAS and DTS data for identifying gas flow.…”
Section: Physical Flow Modellingmentioning
confidence: 99%
“…The DTS data has the potential to detect multiple points of injection and determine gas rate through each injection point. All these are possible as the event is happening and require no shut-in when measuring DTS temperature data [8]. Therefore, DTS helps capture the temperature response throughout the entire length of the well simultaneously as the event is happening.…”
Section: Dts Monitoring Of Well Completion Processesmentioning
confidence: 99%
“…Hermank et al proposed the use of distributed thermal sensing (DTS) and distributed acoustic sensing (DAS) for the gas lift surveillance [12]. The method is less invasive and can provide a precise injection point based on changing temperature and sound signals.…”
Section: Introductionmentioning
confidence: 99%